The Labour Market As A Job-Seeking Contest: Human Capital, Intergenerational Mobility, and Growth - Raimondello Orsini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1998)
With a fixed hierarchy of jobs, workers engage in a rent-seeking game based on their individual levels of human capital, in order to obtain high-paying positions in the social division of labour. The macroeconomic effects of the worker`s quest for privileged positions are studied through the numerical simulation of an OLG model with credit rationing and neural network expectations. The model shows that a higher turnover and higher meritocracy degree in the job-allocation mechanisms is bound to lead to greater economic growth.
Keywords: 330